'Yes we are inclusive': Examining provision for young people with disabilities in community sport clubs. Issue 1 (February 2018) - Jeanes, Ruth; Spaaij, Ramón; Magee, Jonathan; Farquharson, Karen; Gorman, Sean; Lusher, Dean
Highlights: The enactment of inclusion policies is driven by key champions of disability provision within community sport. Enactment of inclusion policies is influenced by a complex array of factors internal and external to clubs. Young people with disabilities generally remain segregated within community sport. Clubs have contradictory understandings of inclusion. Abstract: The last two decades within Australia have witnessed a range of policies and strategies seeking to promote the inclusion of young people with disabilities within mainstream community sport clubs. Whilst research at an institutional level has highlighted the problems with mainstreaming agendas, few studies have examined how grassroots clubs, as key components of the supply side of inclusive provision seek to respond to such policy imperatives. In this paper, therefore, the authors provide a critical analysis of the ways in which clubs engage with inclusion policies in practice. Theoretically, the authors draw on the concept of policy enactment and educational inclusivity. Through analysis of semi-structured interviews with club volunteers, the findings illustrate three key areas. Firstly, the importance of individual volunteers in establishing and developing provision within clubs; secondly, the largely separatist nature of disability provision within clubs; and thirdly, that policies tend to encourage club to focus on narrow forms of participation that lead to competitive pathways and mirror the structure of mainstream sport. In the conclusion, the authors problematize the notion of inclusion presented in policy and practice, suggesting such imperatives do not encourage a holistic approach.